Investigating the Use of Phet Simulation as a Substitute for Practical Tools in Understanding the Concept of Static Electricity - Ismalia, Ismalia; Kusumawati, May; Wahyuni, Putri (International Journal of Education and Teaching Zone, 2022)
The purpose of this research is to see and find out how the understanding of the concept of Static Electricity towards students of SMAN 9 Muaro Jambi Class X MIPA using web-based learning media, namely PhET (Physics Education Technology) simulation. This type of research is quasi-experimental research, where this research involves variables, namely, the independent variable is Phet Simulation, and the dependent variable is class X Sma N 9 Muaro Jambi students. The data collection technique in this study consisted of 20 students taking both tests, learning using Phet Simulation and not using Phet simulation learning (Conventional). In collecting data, the test method was carried out twice, namely the initial test (pre-test) and the final test (post-test). The test instrument used was five questions in the form of an essay. After the test instruments are distributed, the results are obtained where in the pre-test, the average score obtained by students is 40.02, and in the post-test with an average of 85.21, it can be concluded that the practicum media with Phet simulation has an influence on student learning outcomes.